The association between retina thinning and hippocampal atrophy in Alzheimer’s disease and mild cognitive impairment: a meta-analysis and systematic review - Chen, Shuntai; Zhang, Dian; Zheng, Honggang; Cao, Tianyu; Xia, Kun; Su, Mingwan; Meng, Qinggang (Frontiers in Aging Neuroscience, 2023)
Introduction Retina is the "window" of the central nervous system.Previous studies discovered that retinal thickness degenerates through the pathological process in Alzheimer's disease (AD) continuum.Hippocampal atrophy is one of the typical clinical features of AD and had been listed in diagnostic criteria. Former studies had described retinal thinning in normal aging subjects and AD patients, yet the association between retina thickness and hippocampal atrophy in AD is unclear. Thus, we aim to quantify the correlation between these two parameters to identify whether the retina can be a new biomarker for AD early detection.We systematically searched in PUBMED, EMBASE, and Web of Science databases from inception to May 2023 on studies investigating the correlation between retina thickness and hippocampal volume. The newcastle-Ottawa quality assessment scale (NOS) was used to assess the study quality. Pooled correlation coefficient r values were combined after Fisher's Z transformation. Moderator effects was detected through subgroup analysis and meta-regression method.Result Of 1596 citations initially identified, we excluded 1062 studies after screening the titles and abstract(animal models, n=99; irrelevant literatures, n=963). 12 studies met the inclusion criteria, among which 3 studies were excluded for the unextractable data. 9 studies were eligible for this meta-analysis. A positive moderate correlation between the retina thickness was discovered in sum participants of AD, mild cognitive impairment (MCI), and normal control (NC) (r= 0.3469, 95% CI: 0.2490-0.4377, I 2 =5.0%), which was significantly higher than that of the AD group(r= 0.1209, 95% CI:0.0905-0.1510, I 2 =0.0%) (p < 0.05). Among different layers, the peripapillary retinal nerve fiber layer (pRNFL) indicated a moderate positive correlation with hippocampal volume (r= 0.1209, 95% CI:0.0905-0.1510, I 2 =0.0%). The retinal pigmented epithelium (RPE) was also positively correlated (r= 0.1421,95% CI:-0.0447-0.3192], I 2 = 84.1%). The retinal layers and participants were the main overall heterogeneity sources. Correlation in the bilateral hemisphere did not show a significant difference.The correlation is more predominant between RNFL thickness and hippocampal volume in both NC and AD groups than in other layers. Whole retinal thickness is positively correlated to hippocampal volume through all AD continuum, especially in NC and